2017
DOI: 10.1186/s13000-017-0640-5
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of malignant solitary fibrous tumor in prostate with review of the literature

Abstract: BackgroundSolitary fibrous tumor is an uncommon soft tissue neoplasm with intermediate biological behavior, which rarely metastasizes. Malignant solitary fibrous tumor, although not clearly defined, is rarely described in the prostate. The present case is characterized by some peculiarities if compared with previously reported cases of prostatic malignant solitary fibrous tumor. Firstly, it does not show a homogeneous morphology: part of the neoplasm (about 50%) showed the features of a conventional solitary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…According to the World Health Organization, SFTs are classified as intermediate-rare metastatic tumors [5]. The main features of potential malignancy include tumor size (>15 cm), patient age (>55 years), and the presence of mitotic activity > 4/10 high fields of view (×400 magnification) [6]. None of these features was documented in our case, supporting a benign nature of the tumor.…”
Section: Ihc Tumor Markersupporting
confidence: 46%
See 3 more Smart Citations
“…According to the World Health Organization, SFTs are classified as intermediate-rare metastatic tumors [5]. The main features of potential malignancy include tumor size (>15 cm), patient age (>55 years), and the presence of mitotic activity > 4/10 high fields of view (×400 magnification) [6]. None of these features was documented in our case, supporting a benign nature of the tumor.…”
Section: Ihc Tumor Markersupporting
confidence: 46%
“…Immunohistochemically, tumor cells expressed CD34, vimentin, and Bcl-2, showing no expression of smooth muscle actin (SMA), EMA, Cam 5.2, desmin, and calretinin. These findings were compatible with a SFT of the pleura [6]. At the time of diagnosis, imaging of the lower abdomen was not performed.…”
Section: Case Presentationmentioning
confidence: 84%
See 2 more Smart Citations
“…Additionally, SFT and prostatic stromal neoplasms may also share expression for progesterone receptor, smooth muscle actin, CD99 and BCL2. 3,4 Multiple recent studies have reported the presence of a recurrent fusion gene involving NAB2 (a repressor of the transcription factors EGFR1 and EGFR2) and STAT6 (a transcription factor involved in the modulation of interleukin-4 and interleukin-13) in SFTs. 5 The occurrence of this intrachromosomal gene fusion is identified in the majority of SFTs, regardless of location.…”
mentioning
confidence: 99%